Hepatic Arterial Buffer Response and Its Clinical Implications - Sandeep Vaidya; Manjiri Dighe (Association of American Medical Colleges, 2010)
Abstract This resource is a document detailing the hepatic arterial buffer response and its clinical implications. It was created to educate radiologists and clinicians about hepatic arterial buffer response and its implications so as to prevent inaccurate diagnosis of pathology. Reviewing the resource takes about half an hour.